(untitled) (Latakia University Journal -Medical Sciences Series, 2020)
The stability of commercial Rantidine tablets (150 mg) from four local companies and one foreign company was studied. Tablets were exposed to three different conditions of temperature and humidity for six months, and storage on shelf for 12 months. Derivative Spectrophotometry (DS) was used for determination the ranitidine in its tablets. The weight difference method was used to investigate tablets moisture absorption. The results showed change in the color and smell of the tablets by storing in the accelerated conditions, decrease in the content of Rantidine tablets (less than 90%) for all companies, while the C company remained within the specified range. By storing on the shelf the content remained within the range specified, despite the percent degradation ranged between 15-20%. Degradation of Ranitidine increased with temperature and humidity increasing, but the effect of moisture on stability was greater than the effect of temperature. Tablets of all companies, including foreign one, showed an increase in weight because of moisture absorption, which increased with humidity increasing at a constant temperature. This study also showed C company as the best local company in terms of its resistance to degradation and moisture absorption, unlike Company B, which showed rapid and significant degradation compared with other companies.